Optimizing Culture and Tourism in Spurring Local Economic Growth in Bulukumba Regency - Rahman, Abdul (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to analyze the relationship between cultural and tourism factors with local economic growth in Bulukumba Regency. In this study, a quantitative approach was used with data collection through a survey involving respondents from various sectors, including local communities, tourism actors, and local governments. The data were analyzed using statistical methods to identify the influence of culture and tourism on the local economy. The results of the study indicate that cultural activities such as traditional events and the development of tourism infrastructure have a significant contribution to local economic growth, especially in terms of increasing community income and creating jobs. However, the study also underlines the need for improved infrastructure, tourism diversification, and more active community participation to optimize the economic potential derived from the cultural and tourism sectors in Bulukumba Regency.